2020
DOI: 10.1101/2020.12.21.20248409
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

COVID-19 in-hospital mortality in South Africa: the intersection of communicable and non-communicable chronic diseases in a high HIV prevalence setting

Abstract: Background: The interaction between COVID-19, non-communicable diseases, and chronic infectious diseases such as HIV and tuberculosis (TB) are unclear, particularly in low- and middle-income countries (LMIC) in Africa. We investigated this interaction using a nationally representative hospital surveillance system in South Africa. Methods: A national surveillance system for laboratory-confirmed COVID-19 hospital admissions (DATCOV) was established. Using DATCOV data, we describe the demographic characteristic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
30
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 22 publications
(32 citation statements)
references
References 51 publications
1
30
0
1
Order By: Relevance
“…The national surveillance system for COVID-19 hospitalisations conducted by the NICD reported age and underlying medical conditions as potential risk factors for COVID-19 in-hospital mortality. 16 Similar findings were reported from a meta-analysis of clinical characteristics of covid-19 patients in Africa where clinical outcomes directly correlate with the underlying medical conditions and age. 17 Furthermore, this high mortality rate amongst the elderly with comorbidity was also reported from many international studies from France, the United Kingdom and Germany in the same age groups.…”
Section: Discussionsupporting
confidence: 72%
“…The national surveillance system for COVID-19 hospitalisations conducted by the NICD reported age and underlying medical conditions as potential risk factors for COVID-19 in-hospital mortality. 16 Similar findings were reported from a meta-analysis of clinical characteristics of covid-19 patients in Africa where clinical outcomes directly correlate with the underlying medical conditions and age. 17 Furthermore, this high mortality rate amongst the elderly with comorbidity was also reported from many international studies from France, the United Kingdom and Germany in the same age groups.…”
Section: Discussionsupporting
confidence: 72%
“…In addition, as previously reported byJassat et al (2002) that HIV and TB increased the risk of hospital mortality in the general population(40), we found that HIV infection in HCWs was not associated with COVID-19 mortality in HCWs. Antiretroviral (ART) drugs such as tenofovir (TDF) and lopinavir-ritonavir have been found to reduce the risk of severe COVID-19 in people living with HIV(35,41). The lack of association in this study could be that HIV infected HCW may be receiving ART.…”
mentioning
confidence: 68%
“…Pre-wave 1 [aOR 3.0; 95%CI 2.4-3.7)], wave 1 [aOR 2.1; 95%CI (1.8-2.5)] and post-wave 1 [aOR 1.3; 95%CI (1.0-1.7)] were associated with increase in HCW admissions compared to wave 2. There was an increased risk for in-hospital mortality among HCWs in the older age group (40)(41)(42)(43)(44)(45)(46)(47)(48)(49) 95%CI…”
mentioning
confidence: 99%
“…The 10 studies [ 19 , 21 29 ] included 41,113 COVID-19 patients with HIV infection and 18,081,257 COVID-19 patients without HIV infection. Among the 10 included studies, 6 studies [ 21 , 24 26 , 28 , 29 ] were carried out in United States, 2 studies [ 19 , 23 ] were in United Kingdom, and 2 studies [ 22 , 27 ] were in South Africa. Eight studies [ 19 , 21 , 22 , 25 29 ] were designed as a retrospective cohort study and 2 studies [ 23 , 24 ] were designed as a prospective cohort study.…”
Section: Resultsmentioning
confidence: 99%